HUBUNGAN RELAKSASI NAFAS DENGAN PENGURANGAN ANSIETAS PADA IBU HAMIL TRIMESTER III DALAM EVIDANCE BASED MASA KEHAMILAN DI KLINIK JULIANA HARAHAP TAHUN 2024 - Elvi Sepriani; Yetti Atiyah (Excellent Midwifery Journal, 2024)
Anxiety is a taboo that mothers should not experience during pregnancy because it has a negative impact on the fetus, including abnormalities in the fetal brain formation process, inhibiting fetal growth and development, and can cause the mother to experience premature labor. Anxiety in pregnant women can be influenced by environmental conditions and hormonal changes experienced by the mother. Breath relaxation is one method that can reduce anxiety in pregnant women. The aim of this research is to identify the relationship between breath relaxation and reduced anxiety in pregnant women in the third trimester during evidence based pregnancy at the Juliana Harahap clinic in 2024. This type of research is quantitative research using a cross sectional study approach. The population in this study were all pregnant women who visited the Juliana Harahap Clinic for the period September to December 2024. This type of research is quantitative research using a cross sectional study approach. The population in this study were all pregnant women who visited the Juliana Harahap Clinic for the period September to December 2024. The sample was obtained using an accidental sampling technique. The statistical test used was the chi-square test with a confidence level of 95% (α = 0.05). The research results showed that the majority of respondents did breathing relaxation at the Juliana Harahap Clinic in 2024, as many as 25 respondents (100%), the majority of respondents experienced reduced anxiety during pregnancy in pregnant women at the Juliana Harahap Clinic in 2024, as many as 25 respondents (100%), There was a relationship between breathing relaxation and reducing anxiety in pregnant women during pregnancy at the Juliana Harahap Clinic in 2024 with a p value of 0.000 <0.05. It is hoped that pregnant women can relax their breath during pregnancy, especially in the third trimester of pregnancy as preparation for childbirth. Relaxing breathing can help reduce pregnant women's anxiety during pregnancy so that mothers can have a relaxed pregnancy without stress.